AB1110 AUTOINFLAMMATORY DISORDERS ARE COMMON IN PATIENTS WITH MYELODYSPLASTIC SYNDROME AND LINKED TO KARYOTYPE ABNORMALITY AND SOMATIC MUTATIONS STATUS AND A WORSE PROGNOSIS. (June 2019) - Watad, Abdulla; Kacar, Mark; Bragazzi, Nicola Luigi; Zhou, Qiao; Cargo, Catherine; Taylor, Jan; Roman, Eve; Smith, Alexandra; Jones, Richard A.; Amital, Howard; Savic, Sinisa; Mcgonagle, Dennis
Abstract : Background: Many autoinflammatory diseases are associated with mutations in myeloid lineage cells including neutrophils and macrophages. Myelodysplastic syndrome (MDS) is clinically linked to autoinflammatory diseases e.g. Sweets syndrome and NLRP3 inflammasome activation, is an intrinsic feature of some MDS cases. Objectives: We tested the hypothesis that autoinflammatory disease is common in MDS cohorts and we further theorised that MDS with somatic mutations and karyotypic abnormalities were associated with autoinflammation. Methods: 140 MDS patients referred to St. James's University Hospital in Leeds during the period 2012-2018 were systematically and retrospectively recruited with karyotypes and somatic mutations status being performed. Patients with autoinflammation were classified as well-defined autoinflammatory disease or poorly defined "autoinflammatory state" (non-infection related elevated CRP over 10.0 mg/L in 5 consecutive times, taken at separate occasions) based on their final diagnosis and compared in terms of demographic, clinical, laboratory, cytogenetics charts, and outcomes. Results: The average age was 77.08±11 years (median 79 years), with (n=91, 65.0%) male. 72 (51%) patients had an autoinflammatory state and were younger (75.15±11.23 versus 79.15±11.92, p<0.05), and had more frequent arthritis (n=25, 34.7%, versus n=12, 17.6%, p=0.0225), arthralgia (n=32, 44.4%, versus n=18, 26.5%, p=0.0271), skin rash (n=22, 30.6%, versus n=10, 14.7%, p=0.0261), pleuritis (16, 22.2%, versus n=3, 4.4%, p=0.0022). 26.3% of MDS patients with autoinflammatory state had a well-defined autoinflammatory disorder (neutrophilic dermatosis, and polymyalgia rheumatic being the commonest). Mutations affecting the transcription factors pathway (NPM1, RUNX1, BCOR, WTI, TP53, MYD88) (OR 3.15 [95%CI 1.04-9.56], p=0.0426) and deletion of chromosome 5 (OR 3.37 [95%CI 1.01-11.22], p=0.0479) were associated with autoinflammation. Stratifying autoinflammatory state, deletion of chromosome 7 and chromosome 5 were found independent predictors for well-defined autoinflammatory disorder and poorly-defined autoinflammatory state, respectively. Furthermore, acute leukaemia transformation was more frequently in MDS patients with autoinflammatory status (n=25, 34.7%, versus n=8, 11.8%, p=0.0002). Conclusion: Both well-defined and poorly defined autoinflammatory diseases are common in MDS. Transcription factors pathway somatic mutations and abnormal karyotype are associated with the risk of autoinflammation. Autoinflammation is linked to a worse prognosis which may be linked to the higher risk of malignant transformation. Disclosure of Interests: Abdulla Watad: None declared, Mark Kacar: None declared, Nicola Luigi Bragazzi: None declared, Qiao Zhou: None declared, Catherine Cargo: None declared, Jan Taylor: None declared, Eve Roman: None declared, Alexandra Smith: None declared, Richard A. Jones: None declared, Howard Amital Grant/research support from: Pfizer, AbbVie, Janssen, Grant/research support from: Pfizer, AbbVie, Janssen, Consultant for: Pfizer, Merck Sharp & Dohme, Consultant for: Pfizer, Merck Sharp & Dohme, Speakers bureau: Pfizer, Merck Sharp & Dohme, Janssen, Sanofi, Bristol-Myers Squibb, Abbvie, Neopharm, Speakers bureau: Pfizer, Merck Sharp & Dohme, Janssen, Sanofi, Bristol-Myers Squibb, Abbvie, Neopharm, Sinisa Savic Grant/research support from: Novartis and Sobi, Dennis McGonagle Consultant for: Lilly, Novartis UCB, Speakers bureau: Lilly, Novartis UCB